The effectiveness of a promotion programme on hand hygiene compliance and nosocomial infections in a neonatal intensive care unit - Picheansathian W. (2014)
This quasi-experimental study aimed to identify the impact of a promotion programme on hand hygiene practices and its effect on nosocomial infection rates in a neonatal intensive care unit of a university hospital in Thailand. The study populations were 26 nursing personnel. After implementing a hand hygiene promotion programme, compliance with hand hygiene among nursing personnel improved significantly from 6.3% before the programme to 81.2% 7 months after the programme. Compliance rate did not correlate with the intensity of patient care. Nosocomial infection rate did not decrease after the intervention, probably because of the multifactorial nature of infections. All participants agreed that promotion programme implemented in this project motivated them to practise better hand hygiene. This study indicated that multiple approaches and persistent encouragement are key factors leading to a sustained high level of appropriate hand hygiene practices among nursing personnel.